4D Bridge Information Modelling for management of bridge projects: a case study from India. Issue 3 (9th December 2019) - Vilventhan, Aneetha; Rajadurai, R.
Abstract : Purpose: The rapid development of the construction industry requires effective ways to monitor and control the project, and the use of 4D BIM is found to be very efficient. The purpose of this paper is to consider development, application and evaluation of 4D Bridge Information Modelling (BrIM) models for an ongoing bridge project. Design/methodology/approach: An ethnographic action-based case study research methodology is adopted in this study. An ongoing bridge construction project in India is chosen and the 4D BrIM application is evaluated both quantitatively and qualitatively using planned percentage complete (PPC) measurements and semi-structured interviews, respectively. Findings: The evaluation of the case study shows an increase in PPC values from 26.5 to 56.4 per cent after implementation of 4D BrIM in the project. The application of 4D BrIM in the construction phase benefits the project team in material delivery planning, project monitoring and control, construction schedule improvement, documentation and coordination. Practical implications: The developed models are practically applied to the ongoing project and the positive benefits are observed. It is shown that 4D BrIM has the potential to improve the construction of bridge projects. Originality/value: Studies have contributed towards the development and implementation of 3D BrIM models for bridge projects. Limited efforts have been taken to analyse how 4D BrIM models help in the overall management of bridge projects. This study adds value to the existing literature through development, implementation and systematic qualitative and quantitative evaluation of 4D BrIM models.